Technical difficulties and success of endoscopic retrograde colangiopancreatography in a group of patients - Pedro Juan Vázquez González; Marcos Félix Osorio Pagola; Gustavo Becerra Terón; Mayelin González Pérez; Pedro Juan Barrios Fuentes; Denis Monzón Vega; Mabel Vega Galindo (Medisur)
Background: Endoscopic Retrograde Cholangiopancreatography has been effective in the diagnosis and treatment of diseases of the biliopancreatic system. Objective: To determine the grade of technical difficulties and the success of cholangiopancreatography in a group of patients. Methods: prospective, descriptive, observational study that included all the patients who were tested through this procedure from January to December 2009 in the hospital “Dr. Gustavo Aldereguía Lima” from Cienfuegos. Inclusion and exclusion criteria were applied so the sample was composed by 34 patients. In order to define the technical difficulty of this test Madhotra’s difficulty modified test was used. Results: 67,6 % of the patients were males. Age comprised the interval from 31 to 90 years old patients with a mean age of 60.8±16 years. Cholestatic icterus was the predominant medical indication in (55,9 %), followed by choledocholitiasis (26,5 %). Echogram showed normal results in 41,2 % of the patients. The most frequent diagnosis of this test was postcholecystectomy with dilated biliary tract (17,6 %) followed by choledocho and cholelithiasis (14,7 % each one). The grade of technical difficulty was 1 in 91,2 %, grade 2 in 8,8 %. A complete technical success was obtained in 55,9 %, partial success was obtained in 32,3 % and the attempt failed in 11,8 % of the patients. Conclusion: the grade of technical difficulty can influence upon the success of Endoscopic Retrograde Cholangiopancreatography. Its usefulness has been demonstrated with a minimum amount of complications for the patient.